PERCUSSION OF CLOUD COMPUTING ON E-COMMERCE BUSINESSES - SHRASUBATHRA, RANI (International Journal of Psychosocial Rehabilitation, 2020)
Cloud Computing is the magic word which rules entire marketing industries now-a-days. It’s a boon to the world and a very innovative and emerging technology of IT sector.Modern marketing has reached its present stage after undergoing several paces and drastic revolution over the years by continuous pace of changes with the fast evolving technological revolution.Cloud Computing, uses Internet and remote servers to maintain user’s data and applications. It accesses permission to the customers as well as the businesses people to use various applications without installation and access their personal files, data and information at any corner of the world with the help of internet. There are various types of software application are working on the environment of cloud computing service. E-Commerce is became the major service of cloud computing. The primary data for this study is collected by using convenient random sampling method with the sample size of 65 service providers through a questionnaire. This paper was discussed about how E-Commerce business implemented by the cloud computing service. What are all the driving-forces which led to the changes of E-commerce in era of cloud computing, the different types of models like deployment model, delivery models of cloud computing service which are used to attain the target, Traditional E-commerce business models and how these cloud computing and e-commerce models were interconnected were discussed briefly.